Relações dialógicas da crítica literária universitária: sobre Guimarães Rosa e Grande Sertão: Veredas - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The discourse of academic literary criticism is intrinsically related to literary discourse, in which case, the critical aspect refers to the establishment of an analytical and interpretive discourse (the criticism) of other discourses (literary). Thus, we aimed to research "Dialogic relations of university literary criticism: on Guimarães Rosa and Grande Sertao: Veredas" analyzing the dialogic and interdiscursive formation of two cut academic literary criticism Suplemento Literário de/do Minas Gerais, specifically the works O Sertão e Mundo, Antonio’s Candido (1967), and Os Patamares da Fabulação, Walnice’s Galvão (2006) to show the social, historical and ideological of the literary critic article discourse genre, since both were written by university professors and refer the linguistic properties of the work Grande Sertão: Veredas of João Guimarães Rosa. In this sense, the analyzes are based on the theoretical and methodological principles of the dialogic perspective of philosophy of language designed by the Circle of Bakhtin (1981; 1992; 1999; 2006) - especially the notions of dialogue and gender of discourse and also approaches with French Analysis of the Discourse, specifically the contributions of Dominique Maingueneau (2005; 2012) concerning predominantly the literary discourse of ideas, Ethos and interdiscourse. For this, we build speech interfaces university literary criticism with other areas of knowledge, such as Literary Theory, Philosophy, History and the Social Sciences to think about the literary text as discourse. Initially, highlight the conditions of production of university literary criticism, such as the main currents of criticism, discourse genre constitution, fundamentals on the news and ideological criticism. Still, gathered prolegomena for the establishment of a Rosa's discourse, as production conditions mean the Grande Sertão: Veredas position in the historicity of Brazilian literature, the images in the discourse (Ethos) of the author and his work and the reception of these in university. In addition, we discussed the dialogic principle and the rule of interdiscourse, as well as their confluences and epistemological differences to reflect on the proposal for a method of analysis and election of corpus cut criteria. Finally, we selected discursive sequences of both the above critical and analyze the overlapping of the Philological, Stylistic, Marxist, Structuralist and Institutional discourses with the sociological discourse – O Sertão e o Mundo – and speaking of literary criticism – Os Patamares da Fabulação. Found that the operation of the literary critic article genre happens to the extent that the subject is constituted in the discourse, enrolled in an institution (in this case the university), from the sociohistorical and ideological conditions of production that allow valid assessment criteria and non-valid because it arises from the presence of crossings of other discourses in the words.
Dialogic relations of university literary criticism: on Guimarães Rosa and Grande Sertao: Veredas
Keywords: Análise do Discurso; Círculo de Bakhtin; Dialogismo; Interdiscurso; Crítica literária universitária; Discourse analysis; Bakhtin’s circle; Dialogism; Interdiscourse; University literary criticism; LINGUISTICA::FISIOLOGIA DA LINGUAGEM